Ginger Alleviates DSS-Induced Ulcerative Colitis Severity by Improving the Diversity and Function of Gut Microbiota - Guo, Shanshan; Geng, Wenye; Chen, Shan; Wang, Li; Rong, Xuli; Wang, Shuocun; Wang, Tingfang; Xiong, Liyan; Huang, Jinghua; Pang, Xiaobin; Lu, Yiming (Frontiers in Pharmacology, 2021)
The effects of ginger on gastrointestinal disorders such as ulcerative colitis have been widely investigated using experimental models; however, the mechanisms underlying its therapeutic actions are still unknown. In this study, we investigated the correlation between the therapeutic effects of ginger and the regulation of the gut microbiota. We used dextran sulfate sodium (DSS) to induce colitis and found that ginger alleviated colitis-associated pathological changes and decreased the mRNA expression levels of interleukin-6 and inducible nitric oxide synthase in mice. 16s rRNA sequencing analysis of the feces samples showed that mice with colitis had an intestinal flora imbalance with lower species diversity and richness. At the phylum level, a higher abundance of pathogenic bacteria, Proteobacteria and firmicutes, were observed; at the genus level, most samples in the model group showed an increase in Lachnospiraceae_NK4A136_group. The overall analysis illustrated an increase in the relative abundance of Lactobacillus_murinus, Lachnospiraceae_bacterium_615, and Ruminiclostridium_sp._KB18. These increased pathogenic bacteria in model mice were decreased when treated with ginger. DSS-treated mice showed a lower abundance of Muribaculaceae, and ginger corrected this disorder. The bacterial community structure of the ginger group analyzed with Alpha and Beta indices was similar to that of the control group. The results also illustrated that altered intestinal microbiomes affected physiological functions and adjusted key metabolic pathways in mice. In conclusion, this research presented that ginger reduced DSS-induced colitis severity and positively regulated the intestinal microbiome. Based on the series of data in this study, we hypothesize that ginger can improve diseases by restoring the diversity and functions of the gut microbiota.